Resilientes y empoderadas: Representación de la mujer en la literatura colombiana testimonial durante el conflicto armado - Nelly Carolina Millan Hoyos 1994- (2023)
This thesis, which serves to complete the requirements for the degree for M.A (Master of Arts) in Inter-American Studies, from the Faculty of Languages and Cultures of the University of Iceland, is framed in the study of female representation in Colombian testimonial literature written by women about the conflict in the late 20th century. Through a literary and sociocultural theoretical approach, the works Que me busquen en el río (2006) by Adelaida Fernández Ochoa and Las mujeres en la guerra (2000) by Patricia Lara are analyzed. The main objective is to identify the violent context through a female perspective and the characteristics of the female subjects in the narratives. The first part of the thesis addresses the sociopolitical context in Colombia in the 20th century and the representation of women in the conflict. The second part studies testimonial literature and its importance in the country's historical memory. To conclude, the two aforementioned books are analyzed, highlighting how the female characters are portrayed, how they break the traditional schemas of women in Colombia and their participation in the conflict. In conclusion, it is surmised that the two writers manage to rescue the voices of women forgotten in the conflict, breaking traditional generic stereotypes, and signifying historical events. Esta tesis, la cual sirve para completar los requisitos para el título de M.A. (Master of Arts /Maestría) en Estudios Interamericanos, de la Facultad de Lenguas y Culturas de la Universidad de Islandia, se enmarca en el estudio de la representación femenina en la literatura testimonial colombiana escrita por mujeres sobre el conflicto de finales del siglo XX en el país. A través de un enfoque teórico literario y sociocultural, se analizan las obras Que me busquen en el río (2006) de Adelaida Fernández Ochoa y Las mujeres en la guerra (2000) de Patricia Lara. El objetivo principal es identificar el contexto violento a través de una mirada femenina y las características de los sujetos femeninos en las ...